2022
DOI: 10.1007/s11356-021-17940-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential disruptive effects of copper-based antifouling paints on the biodiversity of coastal macrofouling communities

Abstract: In recent years, after the ban on tributyltin (TBT)-based antifouling paints, copper-based paints have become the main coatings for boat hulls due to their e ciency and endurance. Copper(I) compounds like Cu 2 O and CuSCN are used alone or in combination with booster biocides, i.e. Irgarol 1051, chlorothalonil and dichlo uanid. The expanded use of these paints has increased copper leaching into coastal environments, requiring attention and legislative restrictions for potential long-term effects on benthic pop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…One such paint is designed to last 3-5 years, gradually releasing all the incorporated biocides, causing a significant (and global) impact on marine life [25]. A recent experimental study on copper-based paints in the Venice lagoon, for example, revealed that copper released by selected commercial AF paints has potential disruptive effects on the biodiversity of coastal macrofouling communities, affecting both the settlement and growth of key species of macrofouling of hard-substrata [26].…”
Section: Environmental Insightmentioning
confidence: 99%
See 1 more Smart Citation
“…One such paint is designed to last 3-5 years, gradually releasing all the incorporated biocides, causing a significant (and global) impact on marine life [25]. A recent experimental study on copper-based paints in the Venice lagoon, for example, revealed that copper released by selected commercial AF paints has potential disruptive effects on the biodiversity of coastal macrofouling communities, affecting both the settlement and growth of key species of macrofouling of hard-substrata [26].…”
Section: Environmental Insightmentioning
confidence: 99%
“…The fact that Cu + released by copper-based paints in the Venice lagoon has potentially disruptive effects on the biodiversity of coastal macrofouling communities might soon alter the native structure of the benthic communities (those in the lowest level of a body of water) [26]. The Venice lagoon, for example, hosts a broad mussel farming activity.…”
Section: Social Insightmentioning
confidence: 99%
“…Being based on a polymeric binder, they are very resistant to abrasion and for this reason they represent an excellent solution for fast boats or frequently hauled or wheeled ones [ 15 ]. Moreover, they generally have lower costs than self-polishing antifouling paints and, as they suffer less from changes in water conditions, they are also suitable for long navigations [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Over 3-5 years the AF coating applied to the vessel's hull releases all Cu + and booster biocides into seawater significantly impacting marine life including coastal macrofouling communities. 3,4 The leached biocides, indeed, are poorly biodegradable and therefore remain in marine sediments for a long time, harming the aquatic environment. 5,6,7 Research aimed at developing ecofriendly AF paints has been successful and several new "green" paints have been commercialized, 8,9 even though most ecofriendly antifouling coatings are significantly more expensive than conventional self-polishing copper-based paints.…”
Section: Introductionmentioning
confidence: 99%